Subtract, (2 x+8 ) -(-8 x+9)=

Question

Asked 8/6/2013 11:45:26 AM

Updated 10/27/2014 6:34:54 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

itolduso|Points 7377|

Question

Asked 8/6/2013 11:45:26 AM

Updated 10/27/2014 6:34:54 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Rating

3

(2x + 8 ) - (-8x + 9)

= 2x + 8 + 8x - 9;

= 10x - 1

= 2x + 8 + 8x - 9;

= 10x - 1

Added 10/26/2014 10:11:21 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [10/27/2014 6:34:45 AM]

add the polynomials (4p^3+2p^2-6 +3p^3-p+8)=

Question

Not Answered

Updated 6/1/2014 11:28:05 AM

1 Answer/Comment

(4p^3+2p^2-6 +3p^3-p+8) = 7p^3 + 2p^2 - p + 2

Added 6/1/2014 11:28:05 AM

This answer has been confirmed as correct and helpful.

multiply. -5(4 y +3) =____,(simplify your answer, do not factor) **Weegy:**
-5(4y + 3) = -20y - 15
(More)

Question

Not Answered

Updated 7/28/2014 2:38:59 PM

0 Answers/Comments

multiply. -5(4 y +3) =____,(simplify do not factor)

Question

Not Answered

Updated 6/27/2014 1:56:50 AM

3 Answers/Comments

-5(4 y +3) = 20y-15

Solution :

-5(4 y +3)

=((-5))(4y+3)

=(-5)(4y)+(-5)(3)

= 20y-15

Solution :

-5(4 y +3)

=((-5))(4y+3)

=(-5)(4y)+(-5)(3)

= 20y-15

Added 6/27/2014 1:56:50 AM

This answer has been confirmed as correct and helpful.

multiply 9 x(5^2 +9) the product is__? **Weegy:** = x2 + 7x + 10 **User:** simplify your answer **Weegy:** that's not possible! what do you need to know. [s] **User:** : multiply 9 x(5^2 +9) the product is__? **Weegy:** = x2 + 7x + 10 **User:** you need to multiply the monomial by each term of the polynomials be sure t o multiply coefficient and be sure to use the product rule to multiply variable (More)

Question

Not Answered

Updated 7/1/2014 9:03:33 AM

1 Answer/Comment

9x(5^2 + 9)

= 9x(25 + 9)

= 9x(34)

= 306x

= 9x(25 + 9)

= 9x(34)

= 306x

Added 7/1/2014 9:03:33 AM

This answer has been confirmed as correct and helpful.

Subtract the polynomials (6 x^3 y+3 x^4 y^3)-( 4 x^3 y-4 x^4 y^3), do not factor

Question

Not Answered

Updated 6/1/2014 11:27:05 AM

1 Answer/Comment

(6 x^3 y+3 x^4 y^3)-( 4 x^3 y-4 x^4 y^3)

= 7x^4y^3 + 2x^3y

= 7x^4y^3 + 2x^3y

Added 6/1/2014 11:27:05 AM

This answer has been confirmed as correct and helpful.

27,106,719

questions answered

There are no comments.